2019
DOI: 10.3390/s20010089
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Occlusion Stabilization Splint with Stress-Sensor System for Bruxism Diagnosis and Treatment

Abstract: Bruxism is a masticatory muscle activity characterized by high prevalence, widespread complications, and serious consequences but without specific guidelines for its diagnosis and treatment. Although occlusal force-based biofeedback therapy is proven to be safe, effective, and with few side effects in improving bruxism, its mechanism and key technologies remain unclear. The purpose of this study was to research a real-time, quantitative, intelligent, and precise force-based biofeedback detection device based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
1
23
0
4
Order By: Relevance
“…Moreover, a digitally fabricated splint can protect surgical areas that were treated with stem cells in guided bone regeneration within periimplantitis or jaw augmentation; and might need adjustment during healing process [ 54 ]. The secure addition (bonding) of resins to 3D printed appliances may also enable the later integration of sensors, in order to measure biting forces in occlusal splints or insertion torque of implants in drill guides [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a digitally fabricated splint can protect surgical areas that were treated with stem cells in guided bone regeneration within periimplantitis or jaw augmentation; and might need adjustment during healing process [ 54 ]. The secure addition (bonding) of resins to 3D printed appliances may also enable the later integration of sensors, in order to measure biting forces in occlusal splints or insertion torque of implants in drill guides [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main body of this device consisted of three layers: upper, intermediate, and lower, of which the upper and lower layers fabricated with dental resin materials, whereas the intermediate layer was built up with both resin and a piezoresistive-film sensor. The sandwich technique was outlined in a previously published article [ 23 ]. Meanwhile, future exploration and improvements have been conducted based on the foundation of our preliminary research.…”
Section: Methodsmentioning
confidence: 99%
“…Lantada et al designed a bite force sensor for monitoring bruxism based on magnetic near-field communication [ 22 ]. The inputted bite force signals were then converted into digital signals and transmitted by the wireless Bluetooth to a server terminal [ 23 ]. These collected bite force data can be analyzed by deep learning, which is the representative virtual component of AI.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments on patients, it was found that 22.5 kg average force of duration 7.1 s can be generated 3.6 times in one hour [7]. Moreover, occlusal forces during bruxism can be detected by an artificial intelligence algorithm via strain gauge pressure sensors placed inside the mouth [8].…”
Section: Introductionmentioning
confidence: 99%